2000
DOI: 10.1074/jbc.275.24.17979
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Endothelial Nitric-oxide Synthase Activation Requires Capacitative Ca2+ Entry

Abstract: Endothelial nitric-oxide synthase (eNOS), a Ca2؉ /calmodulin-dependent enzyme, is critical for vascular homeostasis. While eNOS is membrane-associated through its N-myristoylation, the significance of membrane association in locating eNOS near sources of Ca 2؉ entry is uncertain. To assess the Ca 2؉ source required for eNOS activation, chimera containing the full-length eNOS cDNA and HA-tagged aequorin sequence (EHA), and MHA (myristoylation-deficient EHA) were generated and transfected into COS-7 cells. The E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
116
0
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 168 publications
(130 citation statements)
references
References 47 publications
(42 reference statements)
13
116
0
1
Order By: Relevance
“…Ca 2+ release from intracellular stores was required for the activation of eNOS by flow and agonists in aorta [31]. Other studies have found that sustained eNOS activation in endothelial cells by agonists required capacitative Ca 2+ entry [41,42]. Our data also show that sustained eNOS activation by bradykinin is dependent on Ca 2+ entry (Fig.…”
Section: Discussionsupporting
confidence: 77%
“…Ca 2+ release from intracellular stores was required for the activation of eNOS by flow and agonists in aorta [31]. Other studies have found that sustained eNOS activation in endothelial cells by agonists required capacitative Ca 2+ entry [41,42]. Our data also show that sustained eNOS activation by bradykinin is dependent on Ca 2+ entry (Fig.…”
Section: Discussionsupporting
confidence: 77%
“…This latter site piqued our interest because there was literature in the nitric oxide synthase field suggesting a role for a calmodulin-binding site in the targeting of nitric oxide synthase to caveolae (17). Furthermore, it has been shown that endothelial nitric oxide synthase is dependent on CCE for its Ca 2ϩ -dependent activity (31,32). We first established that, as with AC6, upon depletion of cellular cholesterol, the response of AC8 to CCE was much reduced.…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, eNOS, by elevating cGMP level, is a likely key upstream player in the signaling mechanism of HO-2 activation. eNOS, a Ca 2+ /calmodulindependent enzyme, is highly regulated by intracellular Ca 2+ [91,92] and, therefore, it is possible that glutamate, via iGluR-mediated Ca 2+ entry and/or protein phosphorylation, initiates eNOS-mediated cGMP-dependent signaling cascade leading to HO-2 activation.…”
Section: Glutamate Receptors In Cerebral Vascular Endothelium and Ho-mentioning
confidence: 99%